Interactive Human Ludo Game to Elevate PHBS Knowledge in School-Age Kids - Lina Mahayaty; Retty Nirmala Santiasari; Taufan Citra Darmawan; Nita Margaret (Health and Technology Journal (HTechJ), 2025)
School-age children face various health challenges due to the suboptimal implementation of Clean and Healthy Living Behavior (PHBS), including irregular handwashing with soap and improper waste disposal. A lack of awareness regarding PHBS is one of the main contributing factors. This study aims to evaluate the effectiveness of an interactive educational approach using the Human Ludo game to enhance PHBS knowledge among school-age children. This research employed a one-group pretest-posttest design, with data analysis conducted using the Wilcoxon test. The results revealed a statistically significant increase in knowledge following the intervention (p-value = 0.000, significance level = 0.005), demonstrating the effectiveness of the Human Ludo game. Its interactive nature fosters active engagement, allowing children to better comprehend and retain health-related concepts. In conclusion, the Human Ludo game significantly improves children's knowledge of PHBS, providing an innovative, engaging, and effective learning method that can be widely applied in school-based health education programs. This game-based learning approach encourages participation, enhances knowledge retention, and promotes healthy behaviors. Future studies should explore the long-term effects of the Human Ludo game on knowledge retention and its potential applications across broader educational topics.